PEMBERITAAN KASUS HUMAN TRAFFICKING DALAM TIGA SURAT KABAR LOKAL NTT (VICTORY NEWS, TIMOR EXPRESS, DAN POS KUPANG EDISI JULI 2017-SEPTEMBER 2017) - Windy Paskawati Soemarno (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2019)
This study aims to analyze the portion and role of the human trafficking in NTT. This research was conducted through dissecting and sorting information on three of local newspaper media in NTT by using the method of qualitative descriptive content analysis and discourse as research procedures that produce descriptive data from the analytical result of the study and analysis of the content library. Also Actor Network Theory as a theoretical review in analyzing data result. Selection technique using the information on the sampling technique in the period July-September 2017. And analysis with news sorting techniques related to human trafficking in NTT on a collection of news from newspaper in period January 2014-September 2017 which are selected according to certain criteria based on the research objectives. Result of the research shows that 1) the portion of the information provided of local newspaper media in NTT was much larger than provide by the Victory News with other media, while Pos Kupang provides the fewest portion, 2) media attention to the issue human trafficking and illegal labor, as well as greater given by Victory News in terms of news, features, and opinions, 3) the role of local newspaper media as a networks of eradication actors for issues related to human trafficking is on the portion of the system and the attention and the press that they thought. In general, Victory News run more function and role as agents of social control and change.